The Impact of Self-conversation Recording to Improve EFL Students’ Fluency: A Quasi-Experimental Research - Islam, Md. Zohorul (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2022)
This article aims at exploring Bangladeshi EFL students’ use of self-conversation recordings and their effectiveness in improving oral fluency. It also explores using Task-Based Language Teaching (TBLT) to enhance students' speaking performance. The study followed a quasi-experimental research design to check the improvement in the student's oral fluency and accuracy. The sample has been selected purposively. The study sample was 50 EFL students studying in the first semester at the Department of English at the Green University of Bangladesh. Students' speaking data were collected using a pre-test at the beginning of the semester and a post-test at the end of the semester. The data were then analyzed using the statistical software SPSS. The result of the study shows that the self-conversation recording by the students can improve their fluency with grammatical accuracy, and the achievement in the fluency of the students from the experimental group was considerably higher than the control group. The average N-gain score of the experimental group students was better than the control group students (.0424>0.205). However, the mean score achieved in the pre-test in the experimental class and control class was (52.14 <59.16), the mean score achieved in the post-test by the experimental group was higher (72.33 >67.40). The paired sample t-test indicates a significant improvement with a t-value of -14.237 and p. value = .000<0.005. Based on the findings, the study recommends that the instructors of the EFL classroom can use self-conversation recordings to improve their students’ fluency.